How Knowledge-Hiding Behavior Among Manufacturing Professionals Influences Functional Interdependence and Turnover Intention - Jena, Lalatendu Kesari; Swain, Deepika (Frontiers in Psychology, 2021)
Objectives: Knowledge hiding is the inappropriate behaviour of employees at the workplace which makes the entire organization suffer a subtle yet significant loss. Lack of sharing makes the journey of learning an arduous process. This in turn gives rise to a series of uncivil behaviours, hence resulting in decrease of functional interdependence (FI). The cascading results toll for a turnover intention (TI), resting only after turnover- an actual separation from the employer. Statistical analysis of the empirical data collected depicts the intensity of influence of FI and TI as a result of the knowledge hiding behavior. Methods: 363 executives employed in 3 public and 2 private manufacturing organisations in eastern India were the respondents in our study. To analyse the difference in variables of the study t-test was carried out. The statistical findings suggest no significant difference among study variables. This specifies that despite considerable difference in levels of management, there was no significant difference in perceiving workplace incivility, knowledge hiding behaviour, functional interdependence and turnover intention items of our instruments. Results: Correlation findings showed negative association between workplace incivility and functional interdependence (r = -.37, p < .01) and a positive association between workplace incivility and turnover intention (r = .32, p < .01). The condensed effect of workplace incivility (β = -.59, p < .001) along with the significance of knowledge hiding behaviour (β = -.68, p < .01), when functional interdependence was the dependent variable, indicated that knowledge hiding behaviour partially mediates the association between workplace incivility and functional interdependence. Similarly, the effect of workplace incivility (β = .43, p < .01), got reduced, while the effect of knowledge hiding behaviour (β = .66, p < .001) was significant when turnover intention was the dependent variable. Conclusion: The effect of knowledge hiding is inversely proportional to FI, whereas sharing a direct relation with TI. An exhaustive data sample and a rigorous statistical analysis may give a clear picture on the amount of impact of TI and FI due to the lack of knowledge sharing and/ or knowledge hiding.